2014
DOI: 10.1140/epjd/e2014-50100-1
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetically induced transparency for a double Fano-profile system

Abstract: Abstract.A Λ-like model of atomic levels involving two auto-ionizing states is considered. The levels are irradiated by two external electromagnetic fields, a strong driving and a weak probing ones. The analytical formula for medium susceptibility shows an additional electromagnetically induced transparency window caused by the second auto-ionizing level. Characteristics of both transparency windows are analyzed depending on parameters of auto-ionizing levels and the external driving field. Manipulation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…But many studies of EIT have already been done by considering the upper excited states as a structured continuum (i.e. presence of an auto-ionizing (AI) state) [35,36,37,38]. van Enk et al have first discussed the model of a Λ-system in which upper excited states are replaced by a flat continuum [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…But many studies of EIT have already been done by considering the upper excited states as a structured continuum (i.e. presence of an auto-ionizing (AI) state) [35,36,37,38]. van Enk et al have first discussed the model of a Λ-system in which upper excited states are replaced by a flat continuum [35].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that optical properties of an Λ-atomic medium change significantly in which upper excited state is replaced by a structured continuum including AI resonances [36]. Quite recently, Dinh et al have studied that the occurrence of an additional EIT window is due to the presence of second AI state [38].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of auto-ionizing states influences considerably many physical effects. For example, autoionization systems have been investigated as media exhibiting electromagnetically-induced transparency [19,20,21]. They have also been applied for slowing down the light propagating through the medium with auto-ionizing states [20].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of auto-ionizing states considerably influences many physical effects. For example, auto-ionization systems have been investigated as media exhibiting electromagnetically-induced transparency [19][20][21]. They have also been applied for slowing down the light propagating through the medium with auto-ionizing states [20].…”
Section: Introductionmentioning
confidence: 99%